Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1152/jappl.2000.88.4.1355
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-type-specific αB-crystallin distribution and its shifts with T3and PTU treatments in rat hindlimb muscles

Abstract: Changes in alphaB-crystallin content in adult rat soleus and extensor digitorum longus (EDL) were examined after 8 wk of 3,5, 3'-triiodothyronine (T(3)) and propylthiouracil (PTU) treatments. Cellular distributions of alphaB-crystallin expression related to fiber type, and distribution shifts with these treatments were also examined in detail from the gray level of reactivity to specific anti-alphaB-crystallin antibody. alphaB-crystallin content in both soleus and EDL muscles was significantly decreased after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
(53 reference statements)
6
21
0
1
Order By: Relevance
“…Otherwise, it seems that the possible function additive above discussion might relate closely to a maintenance of tensegrity of cytoskeletons (Ingber, 1993) against long-lasting tonic contraction. Because all sHSPs are highly expressed in muscle cells, especially in heart (Dubin et al, 1989) and in slow skeletal muscle (fiber-type-dependent expression) (Atomi et al, 2000), the function of these tissues might be related to tonic contraction, to be maintained with endlessly energy-consuming fashion. In addition, a close correlation has been reported between oxidative metabolism and the expression level of αB-crystallin in various cells in rat tissues (Iwaki et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, it seems that the possible function additive above discussion might relate closely to a maintenance of tensegrity of cytoskeletons (Ingber, 1993) against long-lasting tonic contraction. Because all sHSPs are highly expressed in muscle cells, especially in heart (Dubin et al, 1989) and in slow skeletal muscle (fiber-type-dependent expression) (Atomi et al, 2000), the function of these tissues might be related to tonic contraction, to be maintained with endlessly energy-consuming fashion. In addition, a close correlation has been reported between oxidative metabolism and the expression level of αB-crystallin in various cells in rat tissues (Iwaki et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…All type 1 aerobic fi bers (slow-twitch) and about half of type 2 anaerobic fi bers (fast-twitch), corresponding to mostly type 2A fi bers, were positive for αB-crystallin, with more intense staining in type 1 fi bers. Additional studies confi rmed higher expression of αB-crystallin in slow-compared to fast-twitch fi bers (Golenhofen et al 2004 ;Atomi et al 2000 ). Variable expression in different types of skeletal muscle fi bers may account for specifi c fi ber-type degradation, but this would not account for the lack of cardiac involvement, since αB-crystallin levels are comparably high in the heart (Golenhofen et al 2004 ).…”
Section: Differential Functions Of αB-crystallin In Skeletal and Cardmentioning
confidence: 99%
“…M-lines are largely composed of embryonic heart (EH)-myomesin in slow muscles, and M-proteins in fast muscles (Sjöström et al 1982;Schoenauer et al 2008). The protein turnover rate is higher in slow muscles due to higher rates of protein synthesis (Atomi et al 1991b) and higher chaperone contents have also been reported in slow muscle (Atomi et al 2000). 'B-crystallin is one of these chaperone proteins (Fujita et al 2004;Ohto-Fujita et al 2007) that is reported to be rich in the soleus muscle (Atomi et al 1991b;Koh and Escobedo 2004;Sakurai et al 2005).…”
Section: Two Types Of Muscle-related Force Energy and Adaptabilitymentioning
confidence: 99%